PENERAPAN PENDEKATAN BERBASIS TEKS DALAM PEMBELAJARAN MENULIS TEKS BERNUANSA BUDAYA INDONESIA PADA PEMBELAJAR BIPA : Penelitian Subjek Tunggal pada Pembelajar BIPA Tingkat Mahir - Ulinnuha, Annisa (2017)
This research is motivated by BIPA's learner's skill who lack in writing. Some learners think that writing is complicated and difficult. The difficulties that often experienced by the learner is to determine the words, the structure of the text, and how to develop the word. Therefore to develop the learner's potential; in writing. An innovation from learning is needed to get the learner's attention. So, the researcher tried to apply the Genre-Based Approach in learning writing text with Indonesian culture style. So it can provide an alternative with Genre-Based learning to solve the problem. The learning process conducted by the use of the five stages of Genre-Based Approach, that is building the context, modelling and deconstruction of the text, joint construction of the text, independent construction of the text, and linking related text. The method used in this research is a single subject method with A-B-A design. Based on the calculation of data analysis, the result show that there is an improvement in writing skill with Indonesian culture style after applying the Genre-Based Approach. In addition, the results of this research are discussed based on the learning process by using Genre-Based Approach.----- Penelitian ini dilatarbelakangi oleh kemampuan pembelajar BIPA yang masih kurang dalam menulis. Pembelajar BIPA beranggapan menulis merupakan hal yang rumit dan sulit. Kesulitan yang dialami pembelajar BIPA berupa kesulitan dalam menentukan kata, struktur, dan sukar dalam mengembangkan sebuah tulisan. Oleh karena itu, supaya pembelajar BIPA mampu mengembangkan potensinya dalam hal menulis, diperlukan suatu inovasi pembelajaran yang menarik minat pemelajar. Maka, peneliti mencoba menerapkan pendekatan berbasis teks dalam pembelajaran menulis teks bernuansa budaya Indonesia, sehingga mampu memberikan alternatif dengan pembelajaran berbasis teks dalam mengatasi permasalahan kemampuan menulis. Proses pembelajaran dilakukan dengan menggunakan lima tahapan pendekatan berbasis teks, yaitu building the context, modelling and deconstruction of the text, joint construction of the text, independent construction of the text, dan linking related text. Metode yang digunakan dalam penelitian ini adalah metode penelitian subjek tunggal dengan desain A-B-A. Berdasarkan perhitungan analisis data, hasilnya menunjukkan bahwa terjadi peningkatan kemampuan menulis teks bernuansa budaya Indonesia setelah diterapkan pendekatan berbasis teks. Hasil penelitian ini dibahas berdasarkan proses pembelajaran menggunakan pendekatan berbasis teks.